2022
DOI: 10.34133/2022/9857631
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Computational Screening for Bipolar Magnetic Semiconductors

Abstract: Searching ferromagnetic semiconductor materials with electrically controllable spin polarization is a long-term challenge for spintronics. Bipolar magnetic semiconductors (BMS), with valence and conduction band edges fully spin polarized in different spin directions, show great promise in this aspect because the carrier spin polarization direction can be easily tuned by voltage gate. Here, we propose a standard high-throughput computational screening scheme for searching BMS materials. The application of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…discovered several 2D materials with topological flat bands in the 2DMatPedia database; Yang et al identified 9 potential 2D catalysts for the hydrogen evolution reaction . It should be mentioned that in a recent work, Wang and co-workers screened out 11 BMSs from the Materials Project database, but in a three-dimensional form. Therefore, searching from the 2D materials databases is an effective way to discover 2D BMSs.…”
Section: Introductionmentioning
confidence: 99%
“…discovered several 2D materials with topological flat bands in the 2DMatPedia database; Yang et al identified 9 potential 2D catalysts for the hydrogen evolution reaction . It should be mentioned that in a recent work, Wang and co-workers screened out 11 BMSs from the Materials Project database, but in a three-dimensional form. Therefore, searching from the 2D materials databases is an effective way to discover 2D BMSs.…”
Section: Introductionmentioning
confidence: 99%
“…The Δ2/Δ3 of GdS 2 , GdSe 2 and GdSSe monolayers are 1.05/0.71, 0.96/0.47, and 1.03/0.51 eV, respectively. They are all large enough to block spin flipping and larger than the experimentally fabricated EuGe 2 monolayer (0.05 eV) 58,64 and the previously reported CoPtF 6 (0.02 eV), 65 which make GdS 2 , GdSe 2 and GdSSe monolayers excellent candidate materials for constructing bipolar field effect spin filters and spin valves.…”
Section: Resultsmentioning
confidence: 83%
“…When the doping concetration is small, the ground state magnetic structure of MnPSe 3 is AFM. In 2022, Wang et al used high-throughput computational screening scheme, which includes six filters (figure 8), to explore BMSs [51]. They obtained 11 intrinsic BMS materials (1 experimental and 10 theoretical) from nearly 40 000 structures.…”
Section: Doping Induced Bmsmentioning
confidence: 99%